Aprendizagem relacional em indivíduos surdos prélinguais : exclusão, equivalência de estímulos e superseletividade - Garcia, Lucas Tadeu (Universidade Federal de São Carlos, 2015)
conventional verbal behavior may present significant delays on this task. The studies reported in this dissertation investigated discriminative repertoires learning by such individuals aiming at describing these processes, identifying difficulties and contributing to the development of technologies of teaching. Chapter 1 experiment assessed learning by exclusion of conditional discriminations between signs of LIBRAS (Brazilian Sign Language) and pictures and probed for the emergence of speaker repertoires. All participants learned new discriminations by exclusion. Signaling emerged for some but not all participants after learning listener behavior by exclusion. An idiosyncratic verbal repertoire acquired outside from the experimental setting seems to have affected the performance of some participants. In Chapter 2, two experiments evaluated the formation of equivalence classes between signs (set A), pictures (set B) and printed Words (set C) in the same participants. In both experiments, all participants learned the AB baseline relations, responded consistently on symmetry probes (BA) and showed tact responses (BD). In the first experiment of Chapter 2, two out of three participants learned CB baseline discriminations and showed the formation of stimulus equivalence classes. One participant also correctly emitted signs in the presence of printed words (CD). In the second experiment, all three participants learned AB and CB baseline relations, taught with a multiple baseline design across three sets of three words, and showed the formation of nine equivalence classes and the emergency of signaling responses in the presence of printed words. Consistent with previous studies, a rudimentary reading repertoire was taught to five participants via stimulus equivalence. In addition, textual behavior has also emerged for four participants. Chapter 3 experiment aimed to evaluate the occurrence of restricted stimulus control topographies in conditional discriminations learning between printed words and pictures and to develop a procedure to establish adequate stimulus control. Six deaf children were taught three sets of three CB discriminations and were tested for restricted stimulus control. A constructed response matching-to-sample, adapted as a differential observing response (CR-DOR), was used as a remediation procedure for participants who showed overselectivity. CR-DOR was used alone or combined with an identity matching-tosample task between printed words in which S- comparisons showed critical differences in relation to S+. Restrict stimuli control occurred with five out of six participants after they learned CB relations. The CR-DOR procedure, when used alone, was effective in remediating overselectivity with most part of stimulus sets. Although, only the combination of both types of remediation procedures was effective for four children with the first stimulus set. Results showed the importance of evaluating stimulus control topographies while teaching reading repertoires to deaf individuals and suggest that teaching procedures should include such a procedure since the beginning. Taken together, the three studies provided evidence about possible difficulties or potentials these participants may face while acquiring some sorts of relational repertoires and indicated directions for planning effective teaching procedures.
Keywords: Deafness; Learning by Exclusion; Overselectivity; Stimulus Equivalence; Aprendizagem por Exclusão; Equivalência de Estímulos; Controle Restrito; Surdez; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO